THE UTILIZATION OF FLASH CARDS IN TEACHING ENGLISH TO YOUNG LEARNERS - Novi Nuryani; Odo Fadloeli (IKIP Siliwangi, 2021)
Media in learning process is very intact because it will be supported from the learning to be more easily exposed. Many experts say that with the media, it can help teachers and students in the learning process to be able and achieve the goals of the learning process. This research aimed it introducing and describing how the preparation and utilization of the flash cards media are used by teachers in teaching English to young learners. This research was conducted at SDN Baros Mandiri 2 Cimahi. The method used in this research is the descriptive research in accordance with the case study that occurred. The source of the data was the English teacher and the subjects were the second grade students of SDN Baros Mandiri 2 Cimahi. Observation, interviews and documentation are the data collection techniques used in this research. The findings reveal that teachers use flash card media according to the material to be delivered to young learners. Based on the results of the research the flash card media can help facilitate teachers in the delivery of learning material, students are also more enthusiastic, excited and very happy to learn English and very influential in the teaching and learning process. Keywords: instructional media, utilization of instructional media, flash Card